Concrete Type Inference for Code Optimization using Machine Learning with SMT Solving - Ye, Fangke; Zhao, Jisheng; Shirako, Jun; Sarkar, Vivek (Proceedings of ACM on programming languages, 2023)
Despite the widespread popularity of dynamically typed languages such as Python, it is well known that they pose significant challenges to code optimization due to the lack of concrete type information. To overcome this limitation, many ahead-of-time optimizing compiler approaches for Python rely on programmers to provide optional type information as a prerequisite for extensive code optimization. Since few programmers provide this information, a large majority of Python applications are executed without the benefit of code optimization, thereby contributing collectively to a significant worldwide wastage of compute and energy resources. In this paper, we introduce a new approach to concrete type inference that is shown to be effective in enabling code optimization for dynamically typed languages, without requiring the programmer to provide any type information. We explore three kinds of type inference algorithms in our approach based on: 1) machine learning models including GPT-4, 2) constraint-based inference based on SMT solving, and 3) a combination of 1) and 2). Our approach then uses the output from type inference to generate multi-version code for a bounded number of concrete type options, while also including a catch-all untyped version for the case when no match is found. The typed versions are then amenable to code optimization. Experimental results show that the combined algorithm in 3) delivers far superior precision and performance than the separate algorithms for 1) and 2). The performance improvement due to type inference, in terms of geometric mean speedup across all benchmarks compared to standard Python, when using 3) is 26.4× with Numba as an AOT optimizing back-end and 62.2× with the Intrepydd optimizing compiler as a back-end. These vast performance improvements can have a significant impact on programmers’ productivity, while also reducing their applications’ use of compute and energy resources.